'All disease begins in the gut'—the role of the intestinal microbiome in ankylosing spondylitis. Issue 3 (11th September 2021) - Harkins, Patricia; Burke, Eoghan; Swales, Catherine; Silman, Alan
Abstract: Ankylosing spondylitis is a chronic, debilitating arthritis with a predilection for the axial skeleton. It has a strong genetic predisposition, but the precise pathogenetic mechanisms involved in its development have not yet been fully elucidated. This has implications both for early diagnosis and for effective management. Recently, alterations in the intestinal microbiome have been implicated in disease pathogenesis. In this review, we summarize studies assessing the intestinal microbiome in AS pathogenesis, in addition to synthesizing the literature exploring the postulated mechanisms by which it exerts it pathogenic potential. Finally, we review studies analysing manipulation of the microbiome as a potential therapeutic avenue in AS management.